KOMPETENSI PERADILAN AGAMA DALAM PENYELESAIAN PERKARA WANPRESTASI DAN PERBUATAN MELAWAN HUKUM DI PERBANKAN SYARI’AH - Ahmad Nur Qodin (Program Studi Hukum Keluarga Islam, 2016)
The settlement of default and fraud can be reached in two ways, non-litigation and litigation. The regulation on litigation process of default and fraud in Shari‟a banking is not vogue. Initially, the case belongs to the General Court, but later on, the Religious Court has also been granted the same competency. However, Article 49 letter (i) of the Law No 3 year 2006 does not clearly stating that default and fraud become one of the Religious Court‟s competencies. This article aims at analyzing thepossible dualism of competencies.